Go together and you will go far: the QualEnv - Change the Climate project - Rato, V.; Roseta-Palma, C.; Simaens, A.; Farelo, C.; Velada, R.; undefined (2ª Conferência Campus Sustentável (CCS), 2020)
Population growth and increased prosperity, rapid urbanization and globalization are bringing global demand for energy, water and food to a point increasingly beyond the Earth’s carrying capacity. Together with climate change, those pressures are causing significant environmental degradation in many parts of the planet. Latin America (LA) is particularly vulnerable: deforestation of rainforests, climate change-induced loss of land productivity, biodiversity loss, natural resources degradation, water shortages, all have been increasing. The LA region is fully aware of the challenges ahead and in many countries regulatory instruments have been put in place to face them. However, sector-specific policies are generally not integrated, causing a fragmentation that creates additional pressure. The Global Climate Agreement signed in 2015 in Paris and The UN decision (Agenda 2030) on the Sustainable Development Goals (SDGs) constitute urgent calls and drivers for the involvement of Higher Education Institutions. The UNESCO also recognizes that education has a key role for a sustainable future, challenging Universities to take a leadership role in sustainability issues. As universities educate the next generation of decision-makers and influencers, they can have a greater impact on sustainable development than any other single sector in society. They also produce research that can shape the future through technological and social innovation. However, their positive impact and contribution will be marginal unless they commit to continuous improvement and quality assurance in all their activities. Universities' quality assurance systems provide a formal framework to address this challenge, in line with current European and international standards that require HEI to build a strong commitment to quality assurance and continuous improvement. HEI also have a growing concern to achieve and demonstrate an improved environmental performance by implementing stronger controls over their activities that have negative environmental consequences. This requires a solid integration of the environmental aspects with the institutional quality management systems. QualEnv - Change the Climate is an Erasmus+ Plus Key Action 2 project to promote the cooperation for innovation and the exchange of good practices among 14 partner institutions: Iscte (Portugal), Pontifícia Universidade Católica do Rio Grande do Sul (Brazil), Universidad del Norte (Colombia), Universidad de La Sabana (Colombia), Universidad de Costa Rica (Costa Rica), Universidad Nacional (Costa Rica), Universidad de Lima (Peru), Universidad del Pacífico (Peru), Universidad de Guadalajara, (Mexico), Benemérita Universidad Autónoma de Puebla (Mexico), Universidade Federal de Santa Catarina (Brazil), Universidade do Sul de Santa Catarina (Brazil), Politecnico di Torino (Italy), and Goeteborgs Universitet (Sweden). Among all the partners, the project reaches a community of 664 148 students, 38 286 teachers and 31 636 staff. The project addresses the creation and strengthening of quality assurance mechanisms in environmental management, in a way that is consistent with international standards, such as ISO 14001. The project is based on the transfer of experiences, skills and competences among leading universities in sustainability and quality management, as well as high-value educational and training content that can effectively serve to accelerate progress in the implementation of SDGs in Latin-American universities. All QualEnv partner institutions are deeply committed to environmental protection and sustainable development. The universities have put in place initiatives, programs and management tools to deal with quality improvement and sustainability practices both in campus operations and education. There are however common needs related to systematic and integrating procedures delivering a holistic approach to sustainable development in academic activities. The project is starting by three key actions for a detailed diagnosis of the current situation in each university: SDG mapping including operations and campus management, education, research and outreach; an audit on energy and water use, and waste production and management; the estimation of the institutional carbon footprint. The project will then deliver environmental management systems and action plans for all the Latin-American partners. The other major output is a set educational strategies and resources, customized for each context, and based on a prior sustainability awareness assessment using SULITEST.